EDUCATIVE AIMS OF THE SCHOOL AND TEACHER EDUCATION IN BRAZIL: A CRITICAL ANALYSIS OF RESOLUTION CNE/CP N° 2/2019 - Libaneo, Jose Carlos; Santos, Fabiano Antonio dos; Marques, Hellen Jaqueline [UNESP] (Univ Estadual Campinas, Fac Educacao, 2023)
This article investigates the relationship between the content of Resolution CNE/CP n degrees 2/2019, which defines the National Curricular Guidelines for Initial Teacher Education for Basic Education and establishes the BNCTraining, and the globalized clash over educational purposes and school functions. Given that the formulation of educational purposes derives from philosophical and evaluative orientations, with strong ideological impregnation, they involve disputes between different interests of classes and social groups in relation to the purposes and functions of the school, with evident implications for the ordering of the teacher training system. At present, the neoliberal orientation of education for results based on competences and skills in function of the market is in dispute on the one hand; on the other hand, the humanizing and emancipatory orientation of an education aimed at the full development of human capacities, based on cultural and scientific training. After problematizing the content of the aforementioned resolution and positioning it in relation to the clash over the school's educational purposes, the text seeks to formulate another school project and professional teacher training from the perspective of a humanizing, emancipatory and democratic education aimed at human development. The investigation of this problem was carried out through bibliographical and documentary research. The results show the effective opposition between two conceptions of school, curriculum and teacher training with a predominance of the neoliberal perspective and point to the need for resistance and propositional actions by educators who rely on a socio-critical view.
Keywords: Educative aims of the school; Common National Curriculum Base (BNCC); Resolution CNE/CP n; 2/2019; Education for results; Education for human development